2014
DOI: 10.1186/s13023-014-0217-2
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up of folinic acid supplementation for patients with cerebral folate deficiency and Kearns-Sayre syndrome

Abstract: BackgroundKearns-Sayre syndrome (KSS) is a mitochondrial DNA deletion syndrome that presents with profound cerebral folate deficiency and other features. Preliminary data support the notion that folinic acid therapy might be useful in the treatment of KSS patients. Our aim was to assess the clinical and neuroimaging outcomes of KSS patients receiving folinic acid therapy.MethodsPatients: We recruited eight patients with diagnoses of KSS. Four cases were treated at 12 de Octubre Hospital, and the other two case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Although epilepsy appears to be a constant feature of CFD caused by mutations in FOLR1 (encoding folate receptor alpha) or DHFR (encoding dihydrofolate reductase) [33], not all patients with KSS and CFD have epilepsy. Treatment with oral folinic acid is associated with improvements in clinical and neuroimaging features [31,34], suggesting an etiological relationship between CFD and the mitochondrial phenotype in these patients.…”
Section: Cerebral Folate Deficiencymentioning
confidence: 96%
“…Although epilepsy appears to be a constant feature of CFD caused by mutations in FOLR1 (encoding folate receptor alpha) or DHFR (encoding dihydrofolate reductase) [33], not all patients with KSS and CFD have epilepsy. Treatment with oral folinic acid is associated with improvements in clinical and neuroimaging features [31,34], suggesting an etiological relationship between CFD and the mitochondrial phenotype in these patients.…”
Section: Cerebral Folate Deficiencymentioning
confidence: 96%
“…The patients Pt1 and Pt2 had other metabolic deficiencies that have not been reported before in patients with MTO1 gene mutations. Thus, Pt1 had cerebral folate deficiency without abnormalities in brain MRI, unlike it has been demonstrated in other mitochondrial syndromes . Supplementation with folinic acid normalized the biochemical parameters in CSF, as described in cerebral folate deficiency syndrome , but without major changes in her cognitive status.…”
Section: Discussionmentioning
confidence: 70%
“…However, she died at 5.5 years of age. A more recent study reported CFD in eight Spanish patients with KSS [41]. Six patients were treated with 1 mg/kg/day of folinic acid, two cases received 3 mg/kg/day, and two patients refused therapy.…”
Section: Folate Treatment In Mitochondrial Disordersmentioning
confidence: 97%